Modern Technologies for Creating the Thin-film Systems and Coatings - Nikitenkov, Nikolay N. (IntechOpen, 2017)
Development of the thin film and coating technologies (TFCT) made possible the technological revolution in electronics and through it the revolution in IT and communications in the end of the twentieth century. Now, TFCT penetrated in many sectors of human life and industry: biology and medicine; nuclear, fusion, and hydrogen energy; protection against corrosion and hydrogen embrittlement; jet engine; space materials science; and many others. Currently, TFCT along with nanotechnologies is the most promising for the development of almost all industries. The 20 chapters of this book present the achievements of thin-film technology in many areas mentioned above but more than any other in medicine and biology and energy saving and energy efficiency.